A simple way to make tough diamond/metal laminates. Issue 10 (August 2021) - Xuan, Yang; Fromm, Timo; Bruns, Sebastian; Borchardt, Rudolf; Durst, Karsten; Rosiwal, Stefan M.
Abstract: Diamond foils are exceptionally strong yet brittle. One approach to make ceramic foils less susceptible to brittle fracture is to introduce interfaces into the material that provide pathways for crack deflection. In this study, we were able to produce strong yet tough diamond/metal laminates (DMLs) from freestanding diamond foils using a brazing process. The mechanical behavior was characterized via three-point bending (3PB) where the laminates exhibit step-like fracture. Crack deflection at interfaces induces toughening within the laminates. At approx. 3.0 MJ/m 3 diamond/metal laminates exhibit more than twice the fracture energy of monolithic diamond foils while maintaining 90 % stiffness and about 70 % nominal strength. Classical laminate theory (CLT) supports the assessment of the deformation behavior and step-like fracture of diamond/metal laminates. We find that the diamond-to-metal interface plays a critical role: it must be strong enough to enable the transfer of shear stress, while being weak enough to deflect a crack.